A critical analysis of froth transportation models in flotation - Chao Li; Saeed Farrokhpay; Kym Runge; Dee Bradshaw (International Mineral Processing Congress, 2014)
"It is well known that froth phase has a controlling influence on the overall flotation performance. Froth recovery is expected to be affected by froth transportation behaviour. The latter has been represented by different volume balance and energy balance based models. In froth transportation models based on a volume balance, the froth phase is divided into different zones. The total froth residence time is the sum of the time spent in each zone and is dependent on the cell geometry, bubble burst rate and the position that bubbles enter into the froth phase. Alternatively, the froth transportation model based on an energy balance treats the froth phase as a block. In this model, froth height above the concentrate lip is being predicted by minimising the energy of the system which is dependent on the froth geometry, froth stability and froth rheology. The froth height can be used to calculate the froth efficiency of delivering mineralized bubbles from the pulp to the concentrate lip. This paper critically analyses the current models of froth transportation in flotation, and examines the limitations of these models. The importance of froth rheology, which is the resistance to the froth flow towards the discharging weir, in determining froth transportation, is also highlighted."